IN VITRO CHOLESTEROL BINDING AFFINITY OF TOTAL SAPONIN EXTRACTED FROM GLYCYRRHIZA GLABRA - Moghimipour, Eskandar; Kooshapour, Hossein; Rezaee, Saeed; Khalili, Sareh; Handali, Somayeh (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: Saponins are high molecular weight glycosides, consisting of a sugar moiety linked to a triterpene or steroid aglycone. Many saponins are good detergents and produce stable foam in water. Recently, it has been shown that oral administration of some saponins can prevent hypercholesterolemia, the phenomenon which is the result of complex formation with cholesterol. Glycyrrhiza glabra (Licorice) is a grassy plant with a height of 50-100 cm or more. The medicinal organ of the plant is constituted of the roots, containing 3-15 percent triterpene saponins that have many indications such as expectorant, anti-inflammatory, flavoring and foaming agent. The aim of the present study was to extract and characterize total saponin from licorice roots, and also evaluate the possible interaction between the saponin and cholesterol. Methods: The collected roots of the plant were identified, dried, powdered and defatted with petroleum ether in a soxhlet apparatus. The air-dried powder was successively extracted with methanol, n-butanol and diethyl ether. Then foaming power of the extracted Glycyrrhiza glabra total saponin (GTS) was measured using the Ross-Miles foam column method and the index of emulsification (E24) of the extracted saponin was also determined. The results were compared to data from Quillaja saponaria total saponin (QTS), and Tween 80 as a potent synthetic surfactant. Using a Du-Nouy tensiometer, critical micelle concentrations (CMCs) of the saponins were determined by measuring surface tension as a function of surfactant concentration. The effect of complex formation with cholesterol was determined by measuring the changes in surface tension and critical micelle concentrations due to addition of cholesterol in saponin solutions. Results: The results showed that QTS had a relatively good ability to produce stable foam. In the case of reduction of surface tension and emulsification, the extracted total saponin had less power than QTS and Tween 80. The results also showed that the saponins are capable of forming complex with cholesterol. Conclusion: It can be concluded that oral administration of total saponins of G. glabra and Q. saponaria may cause a reduction in cholesterol absorption through gastrointestinal system and finally a reduction in blood cholesterol. Also due to its excellent surface activity, it can be suggested that the total saponin from licorice roots is a suitable substitute for synthetic surfactants in food, drug and cosmetic industries. Key words: Saponin, Glycyrrhiza glabra, cholesterol, Quillaja saponaria